Efecto de Diferentes Dosis de Humus, Fitohormonas y Tiempos de Aplicación en la Producción Primaria del Pasto Arrhenatherum elatius - Edmundo Danilo Guilcapi Pacheco; Miguel Angel Guallpa Calva; Lisseth Paola Ortiz Cruz (European Scientific Journal, ESJ, 2019)
There is the need to provide an alternative source of food for cattle impulse to evaluate the effect of different doses of humus, phytohormones, and application times in the forage production of the Arrhenatherum elatius pasture. This has already been established in edaphoclimatic conditions of the Licto sector. However, it was implemented through 18 treatments, with 3 repetitions, using a completely random block design with a factorial arrangement (3x3x2). The variables analyzed were the plant height, basal cover, aerial cover, the time of occurrence of pre-flowering, and the production of green and dry matter. According to the results, the six evaluated variables did not show statistical differences in response to the independent effect due to the application of 4, 5, and 6 t • ha -1 of humus and 250 cc • ha -1 of gibberellins, cytokinins and ethylene respectively. On the other hand, the frequency of application showed a significant behavior for the variables; plant height, air cover, the time of occurrence of preflowering, and the production of green matter in 7 days. Finally, the interaction between the factors studied in this investigation showed statistical differences with 9 days of anticipation in the occurrence of the prefloración phase when applying 4 t • ha -1 of humus plus 250 cc • ha -1 of ethylene at 7 days of the equalization cut (H4-E-7). Thus, this is in relation to the 52 days of the treatment (H5-E-14), when placing 5 t • ha-1 of humus plus 250 cc • ha -1 of ethylene applied to the 14 days of the equalization cut. La necesidad de brindar una alternativa como fuente de alimento para el ganado impulso evaluar el efecto diferentes dosis de humus, fitohormonas y tiempos de aplicación, en la producción forrajera del pasto Arrhenatherum elatius cultivo ya establecido en condiciones edafoclimáticas del sector de Licto, donde se implementó la presente investigación mediante 18 tratamientos, con 3 repeticiones, utilizando un diseño de bloques completamente al azar con un arreglo factorial: 3x3x2. Las variables analizadas fueron la altura de planta, cobertura basal, cobertura aérea, el tiempo de ocurrencia de la prefloración, la producción de materia verde y seca. Según los resultados, las seis variables evaluadas, no mostraron diferencias estadísticas en respuesta al efecto independiente debido a la aplicación de 4, 5, y 6 t·ha -1 de humus y de 250 cc·ha -1 de giberelinas, citoquininas y etileno respectivamente. En cambio la frecuencia de aplicación, mostró un comportamiento significativo, para las variables; altura de planta, cobertura aérea, el tiempo de ocurrencia de la prefloración y producción de materia verde a los 7 días. Finalmente, la interacción entre los factores estudiados en esta investigación, mostró diferencias estadísticas con 9 días de anticipación en la ocurrencia de la fase de prefloración al aplicar 4 t·ha -1 de humus más 250 cc·ha -1 de etileno a los 7 días del corte de igualación (H4-E-7), en relación a los 52 días del tratamiento (H5-E-14), al colocar 5 t·ha -1 de humus más 250 cc·ha -1 de etileno aplicados a los 14 días del corte de igualación.